Agarose Coated Culture Plate in Tumorsphere Culture of Cervical Cancer Cell Line HeLa: an Alternative to Non Adhesive Culture Plate - Putu Juniartha; Muhammad Rasjad Indra; Hidayat Sujuti; Diana Lyrawati; Tatit Nurseta (Journal of Tropical Life Science, 2016)
Cervical cancer recurs in 90% cases and linked to cancer stem cells that able to self-renew and responsible for recurrence, metastasis, and mortality of cancer. Isolation and identification of cancer stem cells using serum-free medium needs expensive growth factors and consume time. This study try to grow tumor sphere using culture plate coated with 1% agarose as an efficient and economical alternative to non-adhesive culture plate. HeLa cell line was grew in culture plate coated with 1% agarose and non-adhesive culture plate using similar medium and culture condition. Tumor spheres morphology was observed and the colonies were counted in 7 days followed by single cell assay. Tumor spheres then counted for CD133+, CD34+, and Sox2 expression using flowcytometry. Culture plate coated with 1% agarose can be used as an economic and efficient alternative to culture tumor sphere. Using culture plate coated with 1% agarose, the tumor spheres formed in 7 days with similar morphology to non-adhesive culture plate. Tumorsphere had three dimensional – sphere shape that tightly attached, colonized, and overlapped. The tumor sphere colony counts of two plates were statistically have no significant difference (p=0,667). Single cell assay of a tumor sphere shows that it can grow new tumor spheres with similar morphology. The tumor sphere from culture plate coated with 1% agarose express CD133+ and CD34+ as much as 8.78% ± 2.14 and Sox2 as much as 35.30% ± 23.82 whereas tumor sphere from non-adhesive culture plate express CD133+ and CD34+ as much as 62.36% ± 1.06 and Sox2 as much as 98.86% ± 0.56 (p = 0000).